The challenges of co-extraction of animal and plant proteins from transgenic plants for use in food and feed - Aimutis, William R.; Shirwaiker, Rohan A. (Frontiers in Plant Science, 2025)
Growing consumer awareness about health, environment, and animal welfare has pressured the food industry to be less reliant on animal proteins consumed as a whole product or formulated into a variety of foods. While recognizing the benefits of complete animal proteins, consumers are increasingly adding plant-based meat-, dairy-, seafood-, and egg-alternatives to diversify their diets. However, these alternatives still lack quality, flavor, and textural characteristics animal protein consumers are accustomed to. The challenges in producing affordable, sensorily acceptable plant-based protein products begin at harvest and in the initial extraction processes. This review highlights the current state-of-the-art in plant protein extraction and then relates these to potential challenges and opportunities in molecular farming wherein animal genes are inserted into plants to produce animal proteins. Plant protein quality is influenced by plant characteristics, environmental and climatic influences, harvesting, and the initial extraction steps. Many of these steps are well understood by actors across the food supply chain. As society begins preparing for large increases in protein demand over the next two decades, molecular farming has the potential to create novel protein offerings with higher nutritional quality, especially when the animal proteins are co-extracted with plant proteins, to meet consumer expectations. Bio-chemical/pharma industries have pursued animal protein extraction from transgenic plants for three decades, but efforts to produce food protein concentrates and isolates containing both animal and plant proteins are nascent, with most work accomplished in laboratories. We propose considerations to progress this technology from laboratories to commercial scale and highlight the importance of communication and education across the food supply chain, including regulators and policy makers, for acceptance and success of these novel products. There will undoubtedly be resistance, but perseverance to answer many questions needs to be recognized in preparation for meeting the rapid protein demand.